Pemberdayaan Masyarakat dalam Upaya Pencegahan Vektor Penyakit Melalui Pelatihan Pembuatan Karbol Serai di Palangka Raya: Community Empowerment for Preventing Vector Disease by Practical Production of Lemongrass Carbole in Palangka Raya - Wulandari, Meyta; Ngazizah, Febri Nur; Hasanah, Rizka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Vector-borne diseases are influenced by physical, biological, and socio-cultural environmental conditions. Residents of Pahandut Village were chosen as the subjects of service because part of Pahandut Village is located on the edge of the Kahayan River. Therefore, a lot of rubbish carried by the river flows under people's stilt houses and becomes a habitat for mosquitoes, flies, and cockroaches which can transmit diseases to people. Disease vectors can be prevented by keeping the floors of the house clean by using natural ingredients such as lemongrass. Community service activities are expected to increase public knowledge regarding diseases caused by zoonotic vectors, recognize disease-causing insects in the environment, prevent disease vectors, and skills in making lemongrass carbol. Community service participants' knowledge increased as shown by the evaluation of pre-test and post-test scores. Community service participants were 15 people from the Pahandut sub-district with a pre-test average of 36% and a post-test average of 100%. A comparison of the pre-test and post-test scores shows that there is an increase in knowledge after the service activities are carried out. In conclusion, education about preventing disease vectors and the practical production of lemongrass carbole can increase community knowledge and skills in preventing disease vectors.